#TITLE_ALTERNATIVE# - ANWARI (NIM 23297041); Pembimbing: Dr.Ir. Pekik Argo Dahono, MAKBUL
In this researsch, a method to analyze steady-state unbalanced operation of induction motors is proposed. Different from the standard method based on symmetrical component, this method is derived by the voltage change equation. By the voltage equation of induction motors in the reference frame, the change equation of unbalanced current is determined. Thus, the calculated results is added by balanced current. Therefore, stator and rotor unbalanced conditions will be investigated. The calculated results using the proposed method is compared to the simulated results, in order to predict the accuracy of the proposed method. It is found that the proposed method produces good results and, in some cases, the results are almost the same as that of the simulation method.